Specific cholesterol binding drives drastic structural alterations in Apolipoprotein A1 - Ray, Arjun; Thukral, Lipi (The journal of physical chemistry letters, 2018)
Proteins typically adopt a multitude of flexible and rapidly interconverting conformers, many of which are governed by specific protein interaction domains. Whereas disc-shaped oligomeric HDL and its major protein component ApoA1 have been the focus of several investigations, the structural properties of monomeric ApoA1 remain poorly understood. Using tens of independent molecular simulations (>50 μs), we reveal that ApoA1 adopts a compact conformation. Upon the addition of a physiological concentration of cholesterol to ApoA1, the monomeric protein spontaneously formed a circular conformation. Remarkably, these drastic structural perturbations are driven by a specific cholesterol binding site at the C-terminal and a novel cholesterol binding site at the N-terminal. We propose a mechanism whereby ApoA1 opens in a stagewise manner and mutating the N-terminal binding site destroys the open “belt-shaped” topology. Complementary experiments confirm that the structural changes are induced by specific association of cholesterol with ApoA1, not by the nonspecific hydrophobic effect.
Gesehen am 29.05.2019